International trade and exchange rate - Jong Woo Kang (Asian Development Bank (ADB), 2016)
Tepid trade growth since the 2008/2009 global financial crisis (GFC) has been partly attributed to sluggish demand from developed countries. However, data reveals that developing countries play a bigger role in holding back trade growth, while developed countries show quite robust import growth. Post-GFC, the exchange rate volatility has grown significantly. As decomposion of country groups by changes in currency valuation shows, however, local currency depreciation is not contributing to export growth as much as conventional wisdom dictates. On the other hand, countries with appreciating currencies show rising import intensity and significant export growth. This implies that the more countries undergo currency devaluation - the deeper the degree of devaluation and even competitive devaluations - the more likely international trade will grow slower.
Keywords: C23; F10; F31; 330; gravity model; real effective exchange rate; trade volume